2010
DOI: 10.5395/jkacd.2010.35.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of operative techniques between female and male dentists in class 2 and class 5 resin composite restorations

Abstract: This study aimed to assess whether the gender of the dental practitioner affects operative techniques in class 2 and class 5 resin composite restorations. In 2008, a nationwide survey was given to Korean dentists. Total 12,193 e-mails were distributed, 2,632 were opened by recipients, and 840 responses were collected. Of the respondents, 78.9% were male and 21.1% were female. The gender distribution in the age groups between respondents and the total population did not differ (p > 0.05). A chi-square test was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…When dealing with the treatment aspect of dentistry although male and female dentists have different technique styles the end result remained the same. [11] This could be due to the fact that people feel more comfortable about talking about their personal problems with a member of their own sex, this could be due to religious reasons or due to embarrassment, for example, bad breath. Roter et al, 2001, showed that both male and female patients overwhelmingly chose male doctors.…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with the treatment aspect of dentistry although male and female dentists have different technique styles the end result remained the same. [11] This could be due to the fact that people feel more comfortable about talking about their personal problems with a member of their own sex, this could be due to religious reasons or due to embarrassment, for example, bad breath. Roter et al, 2001, showed that both male and female patients overwhelmingly chose male doctors.…”
Section: Discussionmentioning
confidence: 99%